Psychiatric Advance Directives Under the Convention on the Rights of Persons With Disabilities: Why Advance Instructions Should Be Able to Override Current Preferences - Scholten, Matthé; Gieselmann, Astrid; Gather, Jakov; Vollmann, Jochen (Frontiers in Psychiatry, 2019)
Psychiatric advance directives (PADs) are documents by means of which mental health service users can make known their preferences regarding treatment in a future mental health crisis. Many states with explicit legal provisions for PADs ratified the United Nations (UN) Convention on the Rights of Persons with Disabilities (CRPD). While important UN bodies consider PADs a useful tool to promote the autonomy of service users, we argue that an authoritative interpretation of the CRPD by the Committee on the Rights of Persons with Disabilities has the adverse consequence of rendering PADs ineffective in situations where they could be of most use to service users. Based on two clinical vignettes, we show that reasonable clinical recommendations can be derived from a more realistic and flexible CRPD model. Concerns remain about the accountability of support persons who give effect to PADs. We argue that therefore a model that combines supported decision-making with competence assessment is preferable.